2021
DOI: 10.1029/2020ea001607
|View full text |Cite
|
Sign up to set email alerts
|

Present‐Day Activity of the Anninghe Fault and Zemuhe Fault, Southeastern Tibetan Plateau, Derived From Soil Gas CO2Emissions and Locking Degree

Abstract: Key Points:1. Concentrations of soil gas CO2 from the active fault zones were determined 2. Locking degree of different segments of the active faults was inverted 3. CO2 concentrations are correlated with the locking degree of the active faults Accepted ArticleThis article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 86 publications
(193 reference statements)
2
6
0
Order By: Relevance
“…In conclusion, the observation Rn and CO 2 concentration and flux at sites that closer to the fault show higher value (Figure 1), the results are consistent with previous measurement (Ciotoli, 2014; Li et al., 2013; Y. Yang et al., 2021; Yuce et al., 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In conclusion, the observation Rn and CO 2 concentration and flux at sites that closer to the fault show higher value (Figure 1), the results are consistent with previous measurement (Ciotoli, 2014; Li et al., 2013; Y. Yang et al., 2021; Yuce et al., 2017).…”
Section: Discussionsupporting
confidence: 91%
“…At the Xiadian fault zone, the Rn concentration of site SH01, SH03, XC04, XC05 are higher than other sites, and the lowest value were measured at the site SH07; the Rn flux of SH05, SH04, SH01 have higher measurement values; the CO 2 concentration of site SH03, SH04, SH05, SH07, SH08 and the CO 2 flux of site SH01, SH02, SH03, SH04, SH05, SH08 have higher measurement values. In conclusion, the observation Rn and CO 2 concentration and flux at sites that closer to the fault show higher value (Figure 1), the results are consistent with previous measurement (Ciotoli, 2014;Li et al, 2013;Y. Yang et al, 2021;Yuce et al, 2017).…”
Section: Spatial Characters Of the Observation Concentration And Fluxsupporting
confidence: 92%
“…Following the fault activity determination method used in the past, the mean value M), maximum (M max ), minimum (M min ), standard deviation (Std) and relative activity intensity (RAI) of soil gas Rn and CO 2 concentration were calculated. Assume the average of each sample site along each line is the background value B), and The upper limit (A U ) and lower limit (A L ) of abnormal Rn and CO 2 concentration in soil gas were calculated by adding 0.5 times standard deviation to the background mean (Yang et al, 2021;Liu et al, 2022). The measured value higher than the upper limit of the anomaly is regarded as the anomaly value related to the fault, and the ratio of the maximum measured value in the anomaly area to the background value is defined as the RAI (Shao et al, 2012):…”
Section: Data Processingmentioning
confidence: 99%
“…The frequency of seismic activity has been significantly lower than that in the west of Lingwu since 1970. Studies of low gas anomalies in some active fault zones indicated that the high locking degree of the fault constrains the migration of soil gas, whereas the creeping fault with a low locking degree is more favorable for the discharge of gas from deeper layers up toward the surface (Yang et al, 2018;Zhou et al, 2020;Yang et al, 2021). Although gas concentrations are low in the southern segment of the YRF, according to the slip rate inversed by InSAR, there is ~6.8 km locking in the southern segment of the YRF (Zhang et al, 2020), which the risk of strong earthquakes has increased.…”
Section: Gas Migration and Seismic Hazardmentioning
confidence: 99%
“…However, there have been no earthquakes of magnitude greater than or equal to 7 on the Anninghe fault since 1536, and since January 1977, the Anninghe fault has experienced a 30 yr period of quiescence without earthquakes with a magnitude greater than 4.0, forming a seismic gap, so an earthquake of a large magnitude is highly probable in the future (Wen et al., 2008). A number of other studies support this viewpoint, such as slip deficit studies based on global positioning system (GPS) data (Y. C. Li et al., 2021), interseismic coupling studies based on GPS data and interferometric synthetic aperture radar (InSAR) data (Jiang et al., 2015; Y. C. Li, Nocquet, Shan, & Jian, 2021), strain rate research based on GPS data (Q. Wang et al., 2020), seismogenic depth and seismic risk research based on seismic data and deformation data (J. Li et al., 2020), b value distribution studies based on seismic data (Yi et al., 2008), studies based on CO 2 and radon gas emissions (Y. Yang et al., 2018; Y. Yang et al., 2021), and earthquake hazard assessment based on rupture scenarios (Cheng et al., 2021; S. Yao & Yang, 2022).…”
Section: Introductionmentioning
confidence: 99%